2018
DOI: 10.1021/acs.nanolett.8b00197
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of the Reduction Potential of TiO2–x by Fluorination for Efficient and Selective CH4 Generation from CO2 Photoreduction

Abstract: Photocatalytic reduction of CO holds great promises for addressing both the environmental and energy issues that are facing the modern society. The major challenge of CO photoreduction into fuels such as methane or methanol is the low yield and poor selectivity. Here, we report an effective strategy to enhance the reduction potential of photoexcited electrons by fluorination of mesoporous single crystals of reduced TiO. Density functional theory calculations and photoelectricity tests indicate that the Ti impu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
89
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 185 publications
(91 citation statements)
references
References 46 publications
2
89
0
Order By: Relevance
“…Photocatalytic CO 2 reduction performance was evaluated in the presence of H 2 O vapor, involving a gas‐solid heterogeneous reaction in our reaction system. CO and CH 4 were detected as the main products(Figure a), in accordance with previous reports using similar method ,. The generation rates of CO and CH 4 together with CH 4 selectivity are summarized in Figure b.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Photocatalytic CO 2 reduction performance was evaluated in the presence of H 2 O vapor, involving a gas‐solid heterogeneous reaction in our reaction system. CO and CH 4 were detected as the main products(Figure a), in accordance with previous reports using similar method ,. The generation rates of CO and CH 4 together with CH 4 selectivity are summarized in Figure b.…”
Section: Resultssupporting
confidence: 91%
“…Thermodynamically speaking, a semiconductor with more negative conduction band (CB) potential possesses a higher driving force to transfer photogenerated electrons, which is beneficial for deep reduction of CO 2 into CH 4 . For example, Xing et al . recently demonstrated that the yield and selectivity of CH 4 generation from photoreduction of CO 2 were dramatically improved by modulation of the reduction potential of TiO 2‐x .…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that surface‐attached halogen atoms effectively trap photoinduced holes and elongate the charge separation lifetime, resulting in high photocatalytic efficiency . In addition, halogenation slightly up‐shifts the reduction potential of semiconductors . It was verified by DFT calculation that surface F atoms replaced oxygen vacancies and established internal electric fields in TiO 2− x , leading to an upsweep of Ti 3+ impurity level.…”
Section: Designer Semiconductor Nanoparticles For Photocatalytic Co2rrmentioning
confidence: 99%
“…Yin et al. demonstrated that the fluorination of TiO 2− x nanoparticles dramatically increased the efficiency by 13 times and the selectivity from 25.7 % to 85.8 % for CH 4 production …”
Section: Designer Semiconductor Nanoparticles For Photocatalytic Co2rrmentioning
confidence: 99%
“…[9][10][11] For instance, various foreign atoms have been introduced into metal-containing heterogeneousc atalysts to increaset he selectivity in catalytic reactions. [9][10][11] For instance, various foreign atoms have been introduced into metal-containing heterogeneousc atalysts to increaset he selectivity in catalytic reactions.…”
mentioning
confidence: 99%